Beyond the Lyrics: A Semantic Analysis of Hidden Meanings in Ruth B.’s Song “Dandelions - Duma Simanjuntak; Bernieke Damanik (Yayasan Bayt Shufiya Nusantara, 2026)
This study examines the hidden meanings in Ruth B.’s song “Dandelions” through a semantic approach. The study aims to reveal how simple lyrical expressions construct deeper emotional and symbolic meanings beyond their literal interpretation. Employing a qualitative descriptive method, this research analyzes selected lyric lines by focusing on denotative meaning, connotative meaning, metaphor, symbolism, and imagery. The findings show that connotative meaning is the dominant semantic element, indicating that the song communicates its message mainly through implied and emotional meanings rather than direct expression. The word “dandelions” functions symbolically as a representation of fragile hope, wishes, and emotional uncertainty, while the metaphor “I see forever in your eyes” reflects an imagined future and emotional commitment. The analysis also reveals a gradual emotional progression from attraction and idealization to hope, longing, and uncertainty. These findings suggest that the simplicity of the lyrics does not reduce their semantic richness; instead, it strengthens the emotional accessibility of the song. Therefore, this study confirms that popular song lyrics can be examined as meaningful linguistic texts that reflect human emotions, personal desires, and hidden layers of meaning.